Comparative evaluation of propofol in nanoemulsion with solutol and soy lecithin for general anesthesia - Rittes,José Carlos (2016)
ABSTRACT INTRODUCTION: The vehicle for propofol in 1 and 2% solutions is soybean oil emulsion 10%, which may cause pain on injection, instability of the solution and bacterial contamination. Formulations have been proposed aiming to change the vehicle and reduce these adverse reactions. OBJECTIVES: To compare the incidence of pain caused by the injection of propofol, with a hypothesis of reduction associated with nanoemulsion and the occurrence of local and systemic adverse effects with both formulations. METHOD: After approval by the CEP, patients undergoing gynecological procedures were included in this prospective study: control (n = 25) and nanoemulsion (n = 25) groups. Heart rate, noninvasive blood pressure and peripheral oxygen saturation were monitored. Demographics and physical condition were analyzed; surgical time and total volume used of propofol; local or systemic adverse effects; changes in variables monitored. A value of p < 0.05 was considered significant. RESULTS: There was no difference between groups regarding demographic data, surgical times, total volume of propofol used, arm withdrawal, pain during injection and variables monitored. There was a statistically significant difference in pain intensity at the time of induction of anesthesia, with less pain intensity in the nanoemulsion group. CONCLUSIONS: Both lipid and nanoemulsion formulations of propofol elicited pain on intravenous injection; however, the nanoemulsion solution elicited a less intense pain. Lipid and nanoemulsion propofol formulations showed neither hemodynamic changes nor adverse effects of clinical relevance.